The Effects of Baby Massage on Attachment between Mother and their Infants - Ayşe Gürol, PhD, RN; Sevinç Polat, PhD, RN (Elsevier, 2012)
Purpose: This study was conducted to examine the effect of baby massage on attachment between mothers and their newborns. Methods: This study was carried out from June 2008 to February 2010 in a quasi-experimental design (57 in the experimental group, 60 in the control group). Between the dates of the study, all healthy primipara mothers and their healthy babies were included. Data were collected regarding their demographic characteristics and by using the Maternal Attachment Inventory (MAI). All mothers were assessed on the first and the last days of the 38-day study period. In the experimental group, the babies received a 15-minute massage therapy session everyday during the 38 days. Results: There was no significant difference found in the pretest mean value baseline of the MAI score in both groups. The posttest mean values of the MAI of the experimental group mothers (90.87 ± 10.76) were significantly higher than those of control group (85.10 ± 15.50). There was a significant difference between groups (p < .05). Conclusion: The results of the study have shown that baby massage is effective in increasing the mother-infant attachment.